Inovasi Pemasaran Syariah: Strategi Diferensiasi dan Positioning dalam Siklus Daur Hidup Produk - Syahraeni, Syahraeni; Kirana, Ayu Puspa; Sabbar, Sabbar Dahham; Farida, Ida (JES (Jurnal Ekonomi Syariah), 2025)
This study aims to examine Islamic marketing innovation through the integration of differentiation and positioning strategies at each stage of the product life cycle, from introduction to decline. The increasing consumer awareness of quality halal products, coupled with government policies promoting the halal ecosystem, makes the application of Islamic principles in marketing more relevant. The focus of this research is to develop an integrated Islamic marketing approach that combines Islamic principles with marketing strategies to enhance the competitiveness of halal products in both domestic and international markets. The study employs a qualitative method with a literature review. Data collection is carried out through the identification, review, and analysis of literature such as books, articles, and other relevant sources to strengthen findings and provide a comprehensive understanding of Islamic marketing innovation in differentiation strategies, positioning, and product life cycles. The findings indicate that integrating Islamic principles into differentiation and positioning strategies creates sustainable competitive advantages. Islamic-based marketing enhances product quality and brand image, while managing the product life cycle in accordance with Islamic principles ensures relevance and competitiveness in the market. Modifying products, pricing, packaging, and services based on Islamic principles ensures social and economic sustainability.